2020
DOI: 10.1038/s42003-020-01404-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting endothelin 1 receptor-miR-200b/c-ZEB1 circuitry blunts metastatic progression in ovarian cancer

Abstract: Identification of regulatory mechanisms underlying the poor prognosis of ovarian cancer is necessary for diagnostic and therapeutic implications. Here we show that endothelin A receptor (ETAR) and ZEB1 expression is upregulated in mesenchymal ovarian cancer and correlates with poor prognosis. Notably, the expression of ETAR and ZEB1 negatively correlates with miR-200b/c. These miRNAs, besides targeting ZEB1, impair ETAR expression through the 3’UTR binding. ZEB1, in turn, restores ETAR levels by transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…In particular, the interplay between miRNAs and transcriptional regulators has been shown to regulate key developmental events or cell-fate decisions [41][42][43]. In particular, one well-described network motif, the double-negative feedback loop, is thought to regulate many binary cell-fate decisions [42][43][44]. This regulatory mechanism implies that one miRNA targets a transcriptional regulator, which in turn controls the expression of this miRNA and usually acts as a switch between two alternative cell states [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the interplay between miRNAs and transcriptional regulators has been shown to regulate key developmental events or cell-fate decisions [41][42][43]. In particular, one well-described network motif, the double-negative feedback loop, is thought to regulate many binary cell-fate decisions [42][43][44]. This regulatory mechanism implies that one miRNA targets a transcriptional regulator, which in turn controls the expression of this miRNA and usually acts as a switch between two alternative cell states [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, one well-described network motif, the double-negative feedback loop, is thought to regulate many binary cell-fate decisions [42][43][44]. This regulatory mechanism implies that one miRNA targets a transcriptional regulator, which in turn controls the expression of this miRNA and usually acts as a switch between two alternative cell states [42][43][44][45]. In this study, we propose that, in ccRCC, miR-21 and PPAR-α function in a double-negative feedback loop, where miR-21 and PPAR-α mutually repress each other to control lipid metabolism (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, previous studies reported that a bypass of the regular PTPN6 polyadenylation signal allows the transcription of the downstream miR-200c [ 42 ]. miR-200c was known to be involved in the metastasis and invasion of ovarian carcinoma due to its functional regulation of epithelial-to-mesenchymal transition (EMT) [ 43 , 44 ]. Its co-transcription with PTPN6 provides a potential way to target miR-200c in ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple extra-cellular signals can initiate an EMT-related gene expression program through significant cross-talk between co-factors and transcription factors (TF) forming regulatory networks controlling the metastatic cascade [ 5 , 6 ]. In this regard, it has been widely demonstrated that endothelin-1 (ET-1) axis, including the peptide ligand ET-1 and the two G-protein coupled receptors (GPGR; ET A R and ET B R), is a potent inducer of EMT by regulating the EMT-TF, such as Snail and zinc finger E-box binding homeobox 1 (ZEB1), that repress epithelial genes and stimulate the expression of mesenchymal components [ 7 10 ]. ZEB1 is a prime element of a network of TF controlling EMT by directly repressing E-cadherin [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely demonstrated that ZEB1 can participate in double-negative feedback loops with microRNA (miR)-200 family members, strong inducers of epithelial differentiation [ 11 13 ]. Recent evidence in OC has pointed out the role of ET-1/ET A R axis in regulating the ZEB1/miR-200 circuitry [ 10 ]. In particular, our results indicate that ET A R activation by ET-1 promotes OC progression by inducing ZEB1 expression and suppressing miR-200.…”
Section: Introductionmentioning
confidence: 99%